A importância da concept art para animação contemporânea : análise da animação digital em curta metragem 'Torre' (2017) de Nádia Mangolini através dos processos de criação - Souza, Natacha de (2025)
The purpose of this dissertation is to study Concept Arts in digital animation to justify the analysis of the creative process to produce the Brazilian documentary short film in digital animation format “Torre” (2017) by Nádia Mangolini. Based on these objectives, the research is structured in three chapters. The first explores the concepts and particularities of Concept Art, addressing the points that constitute its foundations and already presenting it as the focus of this research. The second chapter explores the methodology of Genetic Criticism in analyzing the visual development of animations, discussing how Concept Art reveals the dynamics of the creative process through preparatory documents. In the third chapter, there is a detailed analysis of the short documentary animation “Tower” (2017), examining the creative process of the artists involved and applying Genetic Criticism to follow the evolution of visual choices, highlighting the crucial role of Concept Art in the development of animation